Magnetic resonance image–guided focused ultrasound robotic system for transrectal prostate cancer therapy - Giannakou, Marinos; Drakos, Theocharis; Menikou, Georgios; Evripidou, Nikolas; Filippou, Antria; Spanoudes, Kyriakos; Ioannou, Leonidas; Damianou, Christakis A. (My University, 2021)
Background: A magnetic resonance image (MRI) guided robotic device for focussed ultrasound therapy of prostate cancer (PC) was developed. The device offers movement in 5 degrees of freedom (DOF) and uses a single-element transducer that operates at 3.2 MHz, has a diameter of 25 mm and focuses at 45 mm. Methods: The MRI compatibility of the system was evaluated in a 1.5 T scanner. The ability of the transducer to create lesions was evaluated in laboratory and MRI settings, on ex vivo pork tissue and in vivo rabbit thigh tissue. Results: Cavitational and thermal lesions were created on the excised pork tissue. In vivo experiments proved the efficacy of the system in ablating muscle tissue without damaging intervening areas. Conclusions: The MRI compatible robotic system can be placed on the table of any commercial MRI scanner up to 7 T. The device has the ability of future use for transrectal focal therapy of PC with the patient in supine position.
Keywords: Focused ultrasound; MRgFUS; MRI; Prostate; Robotic device